Application of Cooperative Learning Model with Flash Card Media to Improve Student Learning Outcomes at SDN Sugihmas in Indonesian Language Learning - Yunanti, Windha (Prosiding University Research Colloquium, 2021)
The purpose of this study was to find out the effect of using the Cooperative Learning model with Flash Card as a means of increasing student concentration and learning outcomes at SD Negeri Sugihmas in the Covid-19 pandemic era. This research uses Classroom Action Research (CAR) with a qualitative approach. A total of 6 students were selected in this study using posttest techniques. Data collection techniques are student report cards and posttest scores with the Cooperative Learning model using Flash Card as a tool. Based on the results of data analysis, it can be concluded that using the Cooperative Learning model with Flash Card aids can increase concentration so that student learning outcomes increase.